Pengaruh Current Ratio (CR) dan Return On Asset (ROA) Terhadap Harga Saham Pada Perusahaan Manufaktur Yang Terdaftar Di Jakarta Islamic Index(JII) Periode 2020-2024 - Febriani, Nabila; Mutia, Agustina (Manajemen Keuangan Syariah, 2026)
This study analyzes the effect of the Current Ratio (CR) and Return on Assets (ROA) on the stock prices of manufacturing companies listed on the Jakarta Islamic Index (JII) for the 2020–2024 period. CR is used as a liquidity indicator, while ROA reflects profitability in generating profit from total assets. This research adopts a quantitative approach using secondary data from annual financial statements and stock closing prices. The sample was selected through purposive sampling, resulting in 8 companies consistently listed on the JII for five years, producing 40 observations. Data analysis was conducted using panel data regression with the Fixed Effect Model (FEM) as the best model, based on the Chow and Hausman tests. The t-test results show that CR has a significant effect on stock prices (p = 0.0118 < 0.05), and ROA also has a significant effect (p = 0.0040 < 0.05). The F-test confirms that CR and ROA simultaneously have a significant effect on stock prices (p < 0.05). These findings indicate that both liquidity and profitability are important considerations for investors in evaluating sharia-based stocks.